Early Pleistocene and Holocene bryozoans from Indonesia - Di Martino, Emanuela; Taylor, Paul D. (Zootaxa, 2018)
This paper describes 40 bryozoan species, comprising one cyclostome and 39 cheilostomes (8 anascan- and 31 ascophoran-grade), obtained from early Pleistocene and Holocene samples from two localities in Indonesia. Five of the cheilostomes are described as new species: Acanthodesia variegata n. sp., Pleurocodonellina javanensis n. sp., Calyptotheca sidneyi n. sp., Characodoma wesselinghi n. sp., and Turbicellepora yasuharai n. sp. All of the remaining species are extant and characterized by a tropical to subtropical Indo-West Pacific distribution.